Salivary Flow Rate Before, During and After Insertion of Complete Denture in Different Age Group: a Comparative study - Devkota , Dibya; Mathema , Suraj Ram Bhakta; Bhusal , Laxman (Europasian Journal of Medical Sciences, 2021)
Background: Increase in salivary flow accompanying complete denture insertion is a well-known phenomenon. Complete dentures act as a mechanical stimulant, increasing salivary flow after insertion. This study compares unstimulated and stimulated salivary flow rates before, during, and after insertion of a complete denture in different age groups. Method: Forty subjects meeting inclusion criteria were selected. Unstimulated saliva was collected first. Stimulation was produced by chewing paraffin wax and collected of saliva in a graduated container. This procedure was carried out before insertion, during insertion, 24 hours after, and 7 days after insertion of complete dentures. The study data were entered, edited, and coded in Microsoft Excel. The unstimulated and stimulated salivary flow rate was compared at different time intervals. Result: Unstimulated salivary rate was lowest before denture insertion with mean values of 0.27ml/minute. The highest flow rate was recorded during denture insertion (mean values of 0.60 ml/minute). The mean unstimulated salivary flow rate 24 hours after denture insertion was higher than 7 days after denture insertion. The mean stimulated salivary rate was lowest before denture insertion (mean values of 0.59 ml/minute). The highest flow rate was recorded during denture insertion (mean values of 0.93 ml/minute). There was a declining trend in salivary flow rate after denture insertion i.e. 0.86 ml/minute to 0.75ml/min after 24 hours and 7 days of denture insertion. A gradual decrease in salivary flow rate with an increase in age was noted but the association of age with salivary flow rates was not statistically significant. Conclusion: There was an increase in both unstimulated and stimulated salivary flow rate after insertion of complete denture and age does not affect salivary flow rates before, during (immediately after), 24 hours after, and 7 days after denture insertion. DOI: https://doi.org/10.46405/ejms.v3i2.318